THE IMPACT ANALYSIS OF PREFETCH IN THE CACHE ON THE MICROPROCESSOR PERFORMANCE - B. Z. Shmeylin (Российский технологический журнал)
Memory access delay has been a major influence on microprocessor systems performance recently. On-chip cache memory application dramatically reduces this delay. Cache prefetching method is one of the basic ones to give the most effective use of memory cache. In the present study we analyze the effect of one of the types of prefetching, especially, the Markov one, on the whole microprocessor-based system performance. The results obtained make it possible to come up with recommendations for the choice of Markov prefetcher parameters setting for both computationally intensive task and data-rich applications.